Petting Zoos as an Unsuspected Source of Pediatric Infections. Issue 4 (3rd January 2023) - Hall, Jaimee M.; Falcon, Isabelle Z.; Elward, Alexis M.; Daniels, Elizabeth A.; Greene, Sarah E.; Cabler, Stephanie S.; Reich, Patrick J.; Storch, Gregory A.
Abstract : Children are at risk for infection following animal exposure at petting zoos owing to suboptimal hand hygiene and frequent hand-to-mucosal surface contact. Public health surveillance is limited, and infectious risk is likely underrecognized. Most reported infections are enteric. Here, we describe two children with unusual, nonenteric infections following petting zoo exposure.